Fertilidade do solo e produtividade do mamoeiro em um argissolo amarelo em função de doses de substâncias húmicas e torta de filtro - Almeida, Dácio Jerônimo de (2017)
The productive potential of the papaya crop stems from factors related to climate, soil and cultivated variety. However, management systems that provide the addition of organic residues to the soil can cause changes in their chemical, physical and biological attributes favoring root system growth and papaya productivity. The present experiment was carried out with the objective of evaluating the effect of the application of humic substances and sugarcane filter cake, on the soil fertility and the productivity of the 'Papaya Golden' papaya crop cultivated in a Yellow Ultisols. The experiment was conducted under field conditions in the municipality of Mamanguape, Paraíba, Brazil, from October / 2014 to October / 2015. The treatments were arranged in randomized blocks with three replications and six plants per plot, using the factorial scheme (4 x 2) + 1, corresponding to four commercial concentrations of humic substances (0, 15, 30 and 45 ml per plant) Soil without and with fertilization with filter cake of sugar cane in the amount of 20 L per plant every 120 days, plus an additional treatment with mineral fertilization (NPK). The relative growth rate of height and diameter, soil macro and micronutrients (P; K; Ca; Mg; Cu; Fe; Zn; Mn; B) and foliar (N; P; K; Ca, Mg, Cu, Fe, Zn, Mn, B). The number of fruits per plant, photosynthetic pigments, productivity and the relative expression of the rbcL, ACC oxidase and invertase genes were also evaluated. The data were submitted to analysis of variance and regression for the doses of humic substances, whereas to compare the presence and absence of filter cake, the F test was used. The additional treatment was compared with the other treatments using the Dunnett test. The relative growth rates of height and diameter increased linearly as a function of doses of humic substances. The filter cake improved the chemical attributes of the soil, with increased levels of P; K; Ca; Cu; Fe; Zn and organic carbon. Leaf nitrogen contents increased with the application of humic substances in comparison to the control. The filter cake increased the number of fruits and productivity. The levels of chlorophyll a and b, carotenoids as well as the relative expression of the rbcL, ACC oxidase and invertase genes studied were higher with filter cake application and the maximum dose of humic substances. The results obtained in this work indicate evidence that organic fertilization can improve nutrient availability and xi physiological responses in 'Papaya Golden' papaya plants. It is recommended the use of 20 L filter cake per plant and the application of 45 ml per plant of humic substances to obtain greater growth and productivity of papaya.